The Relationship between Native and Foreign Language Speaking Proficiency in University Students - Eva Stankova; Renata Chlumska; Dana Zerzanova (National Research University Higher School of Economics, 2022)
Background: There are many factors that affect the development of speaking in a foreign language. Drawing on the theories that state that competencies established in a native language will transfer across foreign languages, this study examines whether there is a relationship between native and foreign language speaking proficiency. Purpose: Although literature research indicates that native and foreign language acquisition processes are interrelated, there is a lack of studies comparing proficiency levels of native and foreign language speaking skills in adult learners. The purpose of this study was to examine the relationship between speaking competences in English as a Foreign Language and Czech as a Native Language in university students. Methods: A between-group design was used to compare two groups of fifty university students at two different levels of their speaking proficiency in English. Both groups were tested in speaking in Czech. Each test was assessed by an analytical rating scale examining four speaking sub-skills: accuracy, discourse, content and paralinguistics. The scores were analyzed using the F-Test for Equality of Variances and T-Test for the Differences between the Means. Findings: The results showed that the group with the lower level of speaking proficiency in English achieved significantly worse scores for their speaking sub-skills in Czech than the group with the higher level of speaking proficiency in English. Implications: The study offers another piece of empirical evidence in support of the theories that state that competencies established in a native language will transfer across foreign languages and suggests the importance of the development of native language competence with regard to later proficiency in a foreign language.